2005
DOI: 10.1007/s00572-005-0026-5
|View full text |Cite
|
Sign up to set email alerts
|

In situ and in vitro colonization of Cathaya argyrophylla (Pinaceae) by ectomycorrhizal fungi

Abstract: Cathaya argyrophylla, a critically endangered conifer, is found to grow at four isolated areas located in subtropical mountains of China. To examine the involvement and usefulness of mycorrhizas for sustaining the population of this tree, we compared the root system, morphology, and structure of mycorrhizal roots of C. argyrophylla, which were collected from a natural stand and an artificial stand, each grown at a different location. More mycorrhizal roots were found for trees from an artificial stand. The pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…The distinct and multibranched hyphae structure was observed using the clearing, bleaching, and staining method. However, the cell walls of the cortex were still very thick, which is similar to that of uninoculated roots of young seedlings of Cathaya argyrophylla in vitro (Vaario et al 2006). Moreover, a well-developed Hartig net structure, the "palmettis", began to develop in root segments 8 weeks after inoculation.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…The distinct and multibranched hyphae structure was observed using the clearing, bleaching, and staining method. However, the cell walls of the cortex were still very thick, which is similar to that of uninoculated roots of young seedlings of Cathaya argyrophylla in vitro (Vaario et al 2006). Moreover, a well-developed Hartig net structure, the "palmettis", began to develop in root segments 8 weeks after inoculation.…”
Section: Discussionmentioning
confidence: 77%
“…Ectomycorrhizal (ECM) fungi are known to play a fundamental role in enhancing the hydromineral nutrition in temperate and boreal forest ecosystems to affect host plant growth (Smith and Read 1997). A previous study (Vaario et al 2006) reported that C. argyrophylla was a typical ECM tree based on in situ and in vitro evidence and established an in vitro mycorrhization system for this tree. However, physiological and biochemical changes that are associated with ECM development remain unknown.…”
mentioning
confidence: 99%
“…However, spores and inoculum of EM fungi (mostly belonging to Scleroderma and Pisolithus) were generally low in abundance in 155 field plantations of Eucalyptus in southern China [321,322]. Mycorrhizal colonization of Cathaya argyrophylla was higher under artificial stands than under natural stands [323,324]. In attempting conservation of this critically endangered conifer, aseptic EM formation between C. argyrophylla root organs/calluses and Cenococcum geophilum was successfully obtained after five weeks [323,324].…”
Section: Effects Of Em Fungi On Nutrient Uptake and Plant Growthmentioning
confidence: 92%
“…Mycorrhizal colonization of Cathaya argyrophylla was higher under artificial stands than under natural stands [323,324]. In attempting conservation of this critically endangered conifer, aseptic EM formation between C. argyrophylla root organs/calluses and Cenococcum geophilum was successfully obtained after five weeks [323,324].…”
Section: Effects Of Em Fungi On Nutrient Uptake and Plant Growthmentioning
confidence: 93%
“…Indeed, most Pinaceae are considered obligate ECM symbionts (Wang and Qiu 2006). The ECM symbiosis has been confirmed in several genera of Pinaceae, including Abies, Cathaya, Cedrus, Larix, Picea, Pinus, Pseudotsuga, and Tsuga (e.g., Vaario et al 2006;Wang and Qiu 2006). Studies of ECM fungal communities associated with Pineaceae in natural forest habitats usually reveal high fungal diversity (Yamada and Katsuya 2001;Lian et al 2006;Matsuda and Hijii 2004;Yu et al 2007).…”
Section: Introductionmentioning
confidence: 94%